Persepsi Dan Daya Terima Masyarakat Terhadap Cookies Gluten-Free Dibandingkan Cookies Konvensional - Hana Laili Nabila Artanti; Agus Ridwan Misbahudin; Rina Asmaul (Politeknik Negeri Ketapang, 2026)
This study discusses the comparison of perceptions and acceptance of gluten-free cookies and conventional cookies as an alternative to gluten-free food. The formulation of the problem in this study is how the initial perception and final acceptance of the community towards both types of cookies. The purpose of this study was to determine the extent of the differences in perception and acceptance of the community before and after being given education and kissing the two products. The method used is a quantitative approach with a pretest-posttest design using a closed questionnaire distributed to 60 respondents of various ages. Data were analyzed using a paired T-test. The results showed that conventional cookies were superior in taste and texture, while gluten-free cookies were preferred in terms of color, aroma, and health perception. After education and tasting, there was a significant increase in the acceptance of gluten-free cookies, especially in terms of health and purchasing interest. The conclusion of this study is that gluten-free cookies have high potential to be accepted by the community if accompanied by education about their benefits as healthy products and the right development formula so that they can increase positive perceptions and acceptance of the community towards this product.